PEMELIHARAAN JARINGAN IRIGASI DAERAH IRIGASI TEGAL KIRI DAN DAERAH IRIGASI GUNTUR UNIT PENGAMATAN TEKNIS OPAK HILIR - , DEKYANUS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Maintenance of Irrigation networks aims to meet the needs of farmers and communities in need of water, through irrigation networks and water existing buildings, to create a balance between the need and availability of water needed to meet all the needs of the people especially farmers. Maintenance of the irrigation network is done by identifying the damage caused to the irrigation channel that will be created later repairs and maintenance planning. Thus the function will be more effective irrigation channels thereby increasing agricultural production and farmers' welfare. Improvement plan based on the results of the channel on the left Tegal Irrigation channels have 2 locations to repair the damage at a cost of Rp. 11,617,154.00 and irrigation areas of Guntur Rp7.503.741, 00.